Pelatihan dan pendampingan budidaya sayur sehat di tengah pandemi guna meningkatkan taraf hidup masyarakat di wilayah Kentingan RW 10 Jebres Surakarta - Purwanto, Djoko; Dewi, Amina Sukma; Haryanto, Budhi; Bonifatius, Dwi Hastjarja Kustijana (Indonesia Berdaya, 2022)
The Community Service activity is intended to provide an alternative to fulfill the needs of healthy vegetables for housewives in the Kentingan area. RW 10 Jebres Surakarta. This activity is intended to help residents in the Kentingan area of RW 10 Jebres, especially in meeting the needs of a variety of healthy vegetables (such as mustard greens, kale, lettuce), and can also economically provide benefits for saving on daily spending, especially vegetables. On the other hand, assistance in the cultivation of healthy, fresh and green organic vegetables is expected to have a positive impact in improving people's lives in the Kentingan area, RW 10 Jebres Surakarta. This Community Service activity is more focused on involving PKK women in the Kentingan area of RW 10 Jebres Surakarta. PKK RW 10 Jebres Surakarta women will later receive training and assistance on organic vegetable cultivation that can be applied in the future